Inhibition of LDH-A by Oxamate Enhances the Efficacy of Anti-PD-1 Treatment in an NSCLC Humanized Mouse Model - Qiao, Tianyun; Xiong, Yanlu; Feng, Yangbo; Guo, Wenwen; Zhou, Yongsheng; Zhao, Jinbo; Jiang, Tao; Shi, Changhong; Han, Yong (Frontiers in Oncology, 2021)
Immunotherapy is a curable treatment for certain cancers, but it is still only effective in a small subset of patients, partly because of the lack of sufficient immune cells in the tumor. It is reported that targeted lactate dehydrogenase (LDH) to reduce lactic acid production can promote the infiltration and activity of immune cells and turn tumors into hot tumors. Therefore, we constructed a humanized mouse model to evaluate the efficacy of using classical LDH inhibitor oxamate and pembrolizumab alone or in combination in non-small cell lung cancer (NSCLC). We found that both oxamate and pembrolizumab monotherapy significantly delayed tumor growth; moreover, combination therapy showed better results. Immunofluorescence analysis showed that oxamate treatment increased the infiltration of CD8+ T cells in the tumor, which might have enhanced the therapeutic effects of pembrolizumab. Treatment of the humanized mice with anti-CD8 abrogated the therapeutic effects of oxamate, indicating CD8+ T cells as the main force mediating the effect of oxamate. In conclusion, Our preclinical findings position that oxamate not only inhibits tumor growth at a high safe dose but also enhances the efficacy of pembrolizumab in Hu-PBMC-CDX mice. Our study also provides a preclinical model for exploring the efficacy of other immune-based combination therapies for NSCLC.